Therapeutic reduction of neurocan in murine intracerebral hemorrhage lesions promotes oligodendrogenesis and functional recovery - Hongmin Li; Samira Ghorbani; Olayinka Oladosu; Ping Zhang; Frank Visser; Jeff Dunn; Yunyan Zhang; Chang-Chun Ling; V. Wee Yong; Mengzhou Xue (Journal of Neuroinflammation)
Abstract Background Intracerebral hemorrhage (ICH) causes prominent deposition of extracellular matrix molecules, particularly the chondroitin sulphate proteoglycan (CSPG) member neurocan. In tissue culture, neurocan impedes the properties of oligodendrocytes. Whether therapeutic reduction of neurocan promotes oligodendrogenesis and functional recovery in ICH is unknown. Methods Mice were retro-orbitally injected with adeno-associated virus (AAV-CRISPR/Cas9) to reduce neurocan deposition after ICH induction by collagenase. Other groups of ICH mice were treated with vehicle or a drug that reduces CSPG synthesis, 4-4-difluoro-N-acetylglucosamine (difluorosamine). Rota-rod and grip strength behavioral tests were conducted over 7 or 14 days. Brain tissues were investigated for expression of neurocan by immunofluorescence microscopy and western blot analysis. Brain cryosections were also stained for microglia/macrophage phenotype, oligodendrocyte lineage cells and neuroblasts by immunofluorescence microscopy. Tissue structural changes were assessed using brain magnetic resonance imaging (MRI). Results The adeno-associated virus (AAV)-reduction of neurocan increased oligodendrocyte numbers and functional recovery in ICH. The small molecule inhibitor of CSPG synthesis, difluorosamine, lowered neurocan levels in lesions and elevated numbers of oligodendrocyte precursor cells, mature oligodendrocytes, and SOX2+ nestin+ neuroblasts in the perihematomal area. Difluorosamine shifted the degeneration-associated functional state of microglia/macrophages in ICH towards a regulatory phenotype. MRI analyses showed better fiber tract integrity in the penumbra of difluorosamine mice. These beneficial difluorosamine results were achieved with delayed (2 or 3 days) treatment after ICH. Conclusion Reducing neurocan deposition following ICH injury is a therapeutic approach to promote histological and behavioral recovery from the devastating stroke.